Determination of Indoor Air Quality (IAQ) parameters in mechanically ventilated lecture halls and hostel room - Ridzuan, Amzar Shahir (2018)
This study focus to determine the Indoor Air Quality (IAQ) parameters between mechanically ventilated lecture halls and hostel rooms of Universiti Malaysia Kelantan Jeli Campus and Universiti Sains Malaysia Engineering Campus and to suggest the best condition to enhance the IAQ. This study measured the concentrations of total volatile organic compound (TVOC), ozone (O3), carbon monoxide (CO) and respirable particulate (PM4) using set conditions. The set condition for lecture halls is based on temperature and the selected temperature range is between 22°C to 26°C. Meanwhile, the set up conditions for hostel room were detennined by fan speed (0, 1, 3 and 5) and open or close windows. Result of the study shows the IAQ of the USM lecture hall was better than UMK as the mean and maximum concentration of TVOC, CO and PM4 were higher in UMK lecture hall, where the mean concentration of TVOC was 340.5 ppb compared with lecture hall USM with mean of250.5 ppb, mean concentration ofCO is 0.821 ppm in UMK and 0.752 ppm in USM, and for mean concentration of PM4 is 0.215 ppm in UMK and 0.200 ppm is USM. In contrast, IAQ was slightly better in UMK hostel room as indicated by lower mean concentration of TVOC and PM4 recorded. TVOC concentrations inside lecture halls and hostel room followed the typical trends characterized by high concentrations in the morning and low in the evening. Meanwhile, CO and PM4 concentrations showed different diurnal trends between lecture halls and hostel room as pollutants concentration were high in the morning due types of mechanical ventilations in lecture hall and hostel rooms. The results of this study suggested that a good IAQ inside an air conditioning lecture hall can be obtained when the temperature is set at 23°C, while the best condition to reduce indoor air pollutants in hostel room is when fan speed is maintain at one to reduce air circulation and windows are closed to avoid outdoor pollutants intrusion.